'Devi Needs those Rituals!' Ontological Considerations on Ritual Transformations in a Contemporary South Indian Srividya Tradition. (20th May 2021) - Hirmer, Monika
Abstract : Negotiations between continuity and discontinuity have characterized Srividya traditions for centuries; these are primarily studied through texts or the juxtaposition of textual prescriptions with observed practices, leaving the process of how Srividya practitioners negotiate esoteric and orthodox tendencies unexplored. Building on extensive fieldwork among practitioners of a contemporary South Indian Srividya tradition, I present the dynamics animating such transformations. Focusing on kalavahana, one of the tradition's central rituals aimed at identifying with Devi, I trace the underlying forces that gradually replace its most esoteric aspects (centred around the body and pleasure) with conventional worship (external or meditative practices), refashioning the tradition as part of mainstream Saktism. While some practitioners conform to the new canon, others, for whom the changes diminish ritual efficacy, secretly continue embodied practices. Through a Foucauldian archaeologico-genealogical analysis, I investigate which regimes of truth and ontological coordinates allow the ritual to change, and which diminish its efficacy. While at first negotiations between continuity and discontinuity appear driven by socio-political motives, ultimately they are governed and legitimized by fundamentally diverging modes of being. A pre-objectified worldview demands embodied experiences (including unconventional practices invoking pleasure) while a dualistic framework endorses representational practices (such as meditation and idol-worship).